Sub-Saharan Africa: Towards better governance and sustainability? - Helmut K. Anheier; Christian Fröhlich; Regina A. List (Global Policy, 2023)
The countries of the Sub-Saharan region have, on average, made significant progress in governance performance, especially in terms of democratic accountability and public goods provision—findings that seem to contradict patterns of state fragility and economic underdevelopment common in the region. This article explores this seeming contradiction and presents in more detail findings from the Berggruen Governance Index regarding the governance performance of five countries, namely Ghana, Kenya, Nigeria, Senegal and South Africa. Lagging state capacity and growing sovereign debt emerge as critical factors, and the article suggests that they may be responsible for the inability of many countries in the region to consolidate gains in governance as well as economic performance.
Keywords: 320